Analisis Penerapan Manjemen Risiko Pembiayaan pada Perbankan Syariah di Indonesia - Choirunnisak; Azka Amalia Jihad; Melia Frastuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses how risk management is implemented in Islamic banking in Indonesia, and how risk management in financing is applied in Islamic banking in Indonesia. This research is a type of library research that focuses on managing qualitative data using descriptive-analytical methods. The results of this study indicate that there are six stages in the implementation of risk management in Islamic banking in Indonesia: 1) Determining the risks associated with products and transactions within the bank. 2). Establishing risk assessment using measurement methods and information systems in risk management. 3). Setting limits or thresholds for risk tolerance. 4) Assigning ratings to the identified risks. 4). Developing a contingency plan in case the bank faces a critical situation. 6) Establishing internal control systems in every aspect of risk management decision-making. There are also six applications of financing risk management in Islamic banking in Indonesia: 1). Identifying risks in all financing, whether related to products or banking activities.2). Considering the financial condition of potential borrowers, including in-depth analysis of their ability to repay on time. 3). Categorizing risks into various defined criteria. 4). Ideally, each bank should have its own system for measuring the risks of financing provided or to be provided to borrowers. 5). Determining the financing period (maturity profile) linked to market conditions that may fluctuate.6). Assessing collateral aspects and the potential for default in repayments.